Application of Sales Forecasting Using The Least Square Method in Web-Based Information Systems - Nurliana Nasution; Dadang Rukmana Sitompul; Walhidayat Walhidayat (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
Technology has become an important role in life, causing the role of computers to be indispensable in various aspects. The presence of technology today is not only in the field of technology but computational methods are also developing. The use of the internet in the aspect of E-commerce (electronic commerce) also plays an important role in the business process cycle. Sale is a major aspect of supporting survival in an industry. Because the high level of sales in an industry/service can compensate let alone provide benefits for the industry. The LEAST Square method is used as an analytical tool for forecasting / predicting sales at the ABDS Store Pekanbaru store. The level of accuracy of the calculation will have an impact on the availability of stock in the store. This method is often used in finding the best parameters of a mathematical model that describes observational data. By using the least squares method, it is expected that the resulting mathematical model can provide a better description of the observation data.